Analisis Fenomena Penyimpangan Sosial: Tawuran Remaja Dalam Teori Anomie Emile Durkheim - Annisa Intan Maharani; Agnes Clara Nainggolan; Istiharoh Istiharoh; Pramasheila Arinda Putri; Riyan Adhitya Pratama (Badan Penerbit STIEPARI Press, 2023)
This study aims to analyze social deviations in the case of brawls committed by adolescents in the theory of Anomie of Emile Durkheim. Qualitative methods with analysis of sources and literature studies are used to collect information and provide a deep understanding of the factors, impact, overcoming the phenomenon of teenage brawl, as well as how its analysis in the theory of anomie of Emile Durkheim. Based on literature analysis, brawls are often caused by various internal and external factors that have a negative impact on families, communities, schools, and adolescents involved in the brawl itself. To overcome this, countermeasures are made so that the individuals involved can avoid violations or deviations from the norm in the future. The results of this study provide an explanation for the connection of Brawl cases with Emile Durkheim's theory of Anomie, which sees that there is instability in the norms that take place in a society that is now no longer cared for.